Philosophy and love : from Plato to popular culture - Secomb, Linnell (Edinburgh University Press, 2007)
Philosophy and Love introduces historical and contemporary philosophical reflections on love. It brings together philosophy with cultural analysis to provide an accessible and engaging account of conventional theories of love as well as the controversial reformulations evident in same-sex desire, cross-cultural love and internet romance. Starting with Plato, but focusing especially on contemporary European philosophy, this book introduces figures such as Nietzsche, Beauvoir, Irigaray, Derrida and Fanon. Explaining these philosophical approaches in clear and accessible terms, Philosophy and Love also engages with cultural productions - ranging from Sappho to Frankenstein, and from Hiroshima Mon Amour to Desperate Housewives - enabling an exchange between philosophical and cultural theories. Love stories are also central to this interdisciplinary book, revealing the ethical and the political as well as the personal implications of lover's discourses. Embracing both the sentimental and the political this deconstructive reading discloses the paradoxes, conflicts and intensities of the love relation. Features Introduces and explains the philosophies for beginners. Focuses on current controversial issues. Provides a philosophical overview alongside examples from popular culture.